Pengaruh Harga, Diferensiasi Produk, dan Lokasi terhadap Keputusan Pembelian di Giant Ekstra Ujung Menteng Bekasi - Imelda Aprileny; Rosita Andriani (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2018)
The purpose of this study was to determine the effect of price, product differentiation and location on purchasing decisions at Giant Ekstra Ujung Menteng Bekasi, partially and simultaneously. The sample in this study were 100 respondents. Data analysis used validity and reliability tests, partial and simultaneous correlation coefficient tests, multiple linear regression analysis, determination coefficients and hypothesis testing. The results of the multiple regression equation = 2.325 + 1.139 X1 + 0.036 X2 + 0.098 X3. In the multiple regression analysis, the constant a is 2.325 which states that if the variables X1, X2, and X3 are constant, then the Y variable is 2.325. The X1 regression coefficient of 1.139 states that every increase in price will increase the scale of purchasing decisions by 1.139 with the assumption that the other variables are constant. . The X2 regression coefficient of 0.036 states that each increase in product differentiation will increase the scale of purchasing decisions by 0.036 with the assumption that other variables are constant. The X3 regression coefficient of 0.098 states that each increase in location will increase the scale of purchasing decisions by 0.098 with the assumption that other variables are constant. The results of the partial determination coefficient show that the effect of price on purchasing decisions is 87.60%. This shows that the price has an influence in increasing purchasing decisions. The effect of product differentiation on purchasing decisions is 3.96%. This shows that product differentiation has an influence in increasing purchasing decisions. The influence of location on purchasing decisions is 15.84%. This shows that location has an influence in increasing purchasing decisions. The results of the multiple determination coefficients show that the effect of price, product differentiation, and location on purchasing decisions is 85.19%. This shows that price, product differentiation, and location have an influence in increasing purchasing decisions. Based on the results of partial and simultaneous hypothesis testing, it shows that price, product differentiation and location have a significant effect on purchasing decisions at Giant Ekstra Ujung Menteng Bekasi.